A kind of silk peptide nano drug-carrying microcrystal and preparation method thereof, asymmetric silk hydrogel with broad-spectrum antioxidant and preparation method and application thereof

By developing nano-drug-loaded microcrystals of silk fibropeptide and broad-spectrum antioxidant silk fibroin asymmetric hydrogels, the problem of healing difficulties in diabetic skin ulcers is solved, effective anti-inflammatory, antioxidant and antibacterial effects are achieved, and the healing of diabetic skin ulcers is promoted.

CN119055829BActive Publication Date: 2025-02-28INNER MONGOLIA MEDICAL UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411545342.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-28
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

There is an oxidative stress state in diabetic skin ulcers, leading to increased inflammation, endothelial dysfunction and neurological lesions. The existing antioxidant drugs have side effects through systemic administration and are difficult to effectively solve the problem of delayed ulcer healing.

Method used

A silk fibropeptide nanodrug-loaded microcrystals were developed to load apigenin-7-O-glucoside through self-assembly technology and combined with silk fibroprotein and nanosilver to prepare a broad-spectrum antioxidant silk fibroprotein to treat diabetic skin ulcers.

Benefits of technology

This hydrogel has anti-inflammatory, antioxidant and antibacterial effects, can effectively remove excessive ROS in the body, reconstruct redox homeostasis, promote the healing of diabetic skin ulcers, and is highly biosafe and easy to use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The present invention provides a silk peptide nano-drug-carrying microcrystal and a preparation method thereof, a broad-spectrum antioxidant silk asymmetric hydrogel and a preparation method and application thereof, and relates to the technical field of composite materials. The silk peptide nano-drug-carrying microcrystal provided by the present invention comprises a silk peptide nano-crystal and apigenin-7-O-glucoside loaded in the silk peptide nano-crystal. The silk peptide nano-drug-carrying microcrystal provided by the present invention has anti-inflammatory and antioxidant effects, high biosafety, can be degraded, has a wide range of sources, and can be produced on a large scale.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of composite materials, and in particular to a silk peptide nano drug-carrying microcrystal and a preparation method thereof, a broad-spectrum antioxidant silk asymmetric hydrogel and a preparation method and application thereof. Background Art

[0002] Diabetic skin ulcers are chronic, difficult-to-heal wounds that often lead to gangrene, amputation, and even increase the risk of death. They are also an important cause of disability in patients worldwide. There are a large number of reactive oxygen species (ROS) in the microenvironment of diabetic skin ulcers. Excessive ROS induce long-term infiltration of immune cells, which in turn produces more ROS, causing an imbalance between oxidation and antioxidant effects in the wound microenvironment, that is, the wound microenvironment is in a state of oxidative stress for a long time. The combined results of oxidative stress, increased inflammation (such as high expression of inflammatory factors such as IL-6 and TNF-α), endothelial dysfunction, and hypercoagulable state of blood cause irreversible damage to diabetic microangiopathy and macroangiopathy. In addition, oxidative stress has an adverse effect on the blood supply, structure, and metabolism of peripheral nerves, which can lead to severe lesions in the peripheral nervous system (including Schwann cells, myelinated axons, and sensory neurons located in the dorsal root ganglia). Axons are rich in mitochondria, which provide direct energy supply to nerves. At the same time, insufficient adenosine triphosphate (ATP) supply to axons may lose transport capacity, further promoting axonal damage and worsening diabetic neuropathy. In the case of insufficient ATP supply, the loss of detoxification ability of excessive oxidative stress leads to axonal oxidative stress damage in patients with hyperglycemia, resulting in axonal degeneration or apoptosis. Vascular lesions and neuropathy lead to delayed healing of diabetic skin ulcers. Non-healing diabetic wounds are more susceptible to infection, further aggravating the non-healing of wounds. Therefore, it is urgent to develop biomaterials or drugs that can reduce the adverse effects of ROS and maintain a balance between oxidation and antioxidant effects for the treatment of diabetic skin ulcers.

[0003] Under normal conditions, the redox balance in cells is maintained by antioxidant enzymes. However, natural enzymes usually involve proteins and RNA molecules, which are susceptible to environmental factors and become inactive or lose their antioxidant function under pathological conditions. At present, some antioxidants are used clinically to treat chronic wounds in diabetic patients. For example, ferulic acid is a natural antioxidant biomaterial derived from fruits and vegetables. It can inhibit lipid oxidation, increase the expression of catalase, superoxide dismutase, glutathionease and serum zinc and copper, and can effectively improve the healing process of diabetic ulcers; α-fatty acids inhibit the development of diabetic neuropathy by clearing ROS, regenerating endogenous and exogenous antioxidants, repairing oxidized proteins and regulating gene transcription. It is widely used in the treatment of diabetic microangiopathy in clinical practice. Although these drugs have achieved some results in the treatment of diabetic skin ulcers, they are clinically treated by systemic administration, with large drug dosages and many side effects. In recent years, with the continuous development of nanotechnology, many artificially synthesized "nanozymes" have been widely used in the study of antioxidant effects. Researchers have found that nano-structured "nanozymes" can efficiently and stably remove excessive ROS in the body. However, most existing nanomaterials are non-degradable and pose potential dangers when they enter the body. Summary of the invention

[0004] In view of this, the purpose of the present invention is to provide a silk peptide nano-drug-loaded microcrystal and a preparation method thereof, a broad-spectrum antioxidant silk asymmetric hydrogel and a preparation method and application thereof. The silk peptide nano-drug-loaded microcrystal provided by the present invention has anti-inflammatory and antioxidant effects, high biosafety, and is degradable.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The invention provides a silk peptide nano drug-carrying microcrystal, comprising a silk peptide nano microcrystal and apigenin-7-O-glucoside loaded in the silk peptide nano microcrystal.

[0007] Preferably, the mass ratio of the silk peptide nanocrystals to apigenin-7-O-glucoside is 1:0.01-0.5.

[0008] The present invention provides a method for preparing the silk peptide nano-drug-carrying microcrystals described in the above technical solution, comprising the following steps: mixing an apigenin-7-O-glucoside solution with a silk peptide nano-crystal solution, and performing self-assembly to obtain silk peptide nano-drug-carrying microcrystals.

[0009] The present invention provides a method for preparing a broad-spectrum antioxidant silk fibroin asymmetric hydrogel, comprising the following steps:

[0010] A solution of silk fibroin peptide nano-drug-carrying microcrystals, a silk fibroin solution and a nano-silver solution are mixed to obtain a mixed solution; the silk fibroin peptide nano-drug-carrying microcrystals are the silk fibroin peptide nano-drug-carrying microcrystals described in the above technical solution or the silk fibroin peptide nano-drug-carrying microcrystals prepared by the preparation method described in the above technical solution;

[0011] A voltage is applied to the mixed solution to obtain a broad-spectrum antioxidant silk asymmetric hydrogel.

[0012] Preferably, the mass ratio of the silk fibroin peptide nano-drug-carrying microcrystals to the silk fibroin in the silk fibroin solution is 0.02-0.2:1.

[0013] Preferably, the mass ratio of the silk peptide nano drug-carrying microcrystals to the nanosilver in the nanosilver solution is 2-20:1-10.

[0014] Preferably, the mixing comprises: dropping a solution of silk peptide nano-drug-carrying microcrystals into a silk fibroin solution, and then adding a nano-silver solution.

[0015] Preferably, the voltage is 10-100 V; and the voltage application time is 30-300 min.

[0016] The present invention provides a broad-spectrum antioxidant silk asymmetric hydrogel prepared by the preparation method described in the above technical scheme, wherein the broad-spectrum antioxidant silk asymmetric hydrogel has a dense surface and a loose surface; the porosity of the dense surface is 20-40%; and the porosity of the loose surface is 50-80%.

[0017] The present invention provides the use of the broad-spectrum antioxidant silk asymmetric hydrogel described in the above technical solution in the preparation of dressings.

[0018] The silk peptide nano drug-carrying microcrystals provided by the invention have anti-inflammatory and antioxidant effects, high biological safety and are degradable.

[0019] The present invention uses a layer-by-layer self-assembly technique to load apigenin-7-O-glucoside (AG) with silk peptide to prepare silk peptide nano drug-loaded microcrystals (β-nano drug-loaded microcrystals, named β-crystallite / AG). The preparation method of the silk peptide nano drug-loaded microcrystals provided by the present invention has a wide range of raw material sources, simple process, simple operation, can be mass-produced, and has low production cost.

[0020] The present invention mixes a β-crystallite / AG solution, a silk protein solution and a nanosilver solution, adds a uniform electric field, and prepares a broad-spectrum antioxidant silk asymmetric hydrogel rich in β-folded structure ROS response. The broad-spectrum antioxidant silk asymmetric hydrogel prepared by the present invention has a dense topological structure on one side and a loose one side. The dense structure prevents excessive evaporation of moisture from the wound surface and prevents microorganisms in the air from invading the wound surface, thereby reducing the risk of secondary infection of the wound surface; the loose surface has an interpenetrating pore structure, and the loose porous structure can not only quickly absorb excess body fluids, but also facilitate the delivery of oxygen and nutrients to the wound surface. The physicochemical properties of SF@β-crystallite / AG-Ag are evaluated by topological structure, mechanical properties, drug control and release function, antibacterial function and biocompatibility. The ability to scaveng three representative free radicals of ROS (hydrogen peroxide, hydroxyl radical and superoxide anion), intracellular ROS scavenging ability and cellular level anti-inflammatory evaluation. The full-thickness skin defect model of type 2 diabetic rats was used to evaluate the repair effect of SF@β-crystallite / AG-Ag on diabetic difficult-to-heal wounds. This study provides a new method and treatment strategy for the clinical treatment of diabetic difficult-to-heal wounds.

[0021] The broad-spectrum antioxidant silk asymmetric hydrogel prepared by the present invention can remove excess intracellular ROS without interfering with endogenous antioxidant effects, reconstruct redox homeostasis, and avoid cell damage; it can effectively improve the oxidative stress response of the microenvironment of diabetic difficult wounds, reduce inflammatory reactions, promote angiogenesis in diabetic skin tissues, accelerate the healing of diabetic wounds, and has good antibacterial properties. The broad-spectrum antioxidant silk asymmetric hydrogel is simple to use, has high biosafety, can effectively remove excess ROS, and has important potential in the treatment of diabetic ulcers. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 Characterization diagram of the colloidal white solution containing silk peptide nano-drug-carrying microcrystals prepared in Example 1, wherein A is an infrared spectrum diagram, B is an atomic force microscope diagram, and C is a transmission electron microscope diagram;

[0023] Figure 2 The transmission electron microscope image of the nanosilver solution prepared in Example 1;

[0024] Figure 3 The topological structure characterization of the broad-spectrum antioxidant silk asymmetric hydrogel (SF@β-crystallite / AG-Ag) prepared in Example 1, wherein A is the loose surface and B is the dense surface;

[0025] Figure 4 The mechanical properties of the broad-spectrum antioxidant silk asymmetric hydrogel prepared in Example 1 were tested;

[0026] Figure 5 The release curves of the broad-spectrum antioxidant silk asymmetric hydrogel drug and gauze-AG-Ag prepared in Example 1;

[0027] Figure 6 The biosafety test results of the broad-spectrum antioxidant silk asymmetric hydrogel, SF@β-crystallite, SF and control prepared in Example 1 are shown in Figure 1, where A represents cytotoxicity and B represents intradermal sensitization;

[0028] Figure 7 The ability of the broad-spectrum antioxidant silk asymmetric hydrogel prepared in Example 1 to scavenge hydrogen peroxide;

[0029] Figure 8 The ability of the broad-spectrum antioxidant silk asymmetric hydrogel prepared in Example 1 to scavenge hydroxyl radicals;

[0030] Fig. 9 The ability of the broad-spectrum antioxidant silk asymmetric hydrogel prepared in Example 1 to scavenge superoxide anions;

[0031] Fig.10 The ability of the broad-spectrum antioxidant silk asymmetric hydrogel prepared in Example 1 to remove intracellular ROS, wherein A is an intracellular reactive oxygen species fluorescence image, and B is a statistical image of the intracellular reactive oxygen species fluorescence intensity;

[0032] Fig.11 This is a photo of the broad-spectrum antioxidant silk asymmetric hydrogel prepared in Example 1 treating full-thickness skin damage in diabetic rats;

[0033] Fig.12 This is a flow chart for the preparation of silk peptide drug-loaded nanocrystals. DETAILED DESCRIPTION

[0034] The invention provides a silk peptide nano drug-carrying microcrystal, comprising a silk peptide nano microcrystal and apigenin-7-O-glucoside loaded in the silk peptide nano microcrystal.

[0035] In the present invention, the size of the silk peptide nanocrystals is preferably 50-400nm, more preferably 150-200nm. In the present invention, the silk peptide is a crystalline region of natural silk protein composed of a specific amino acid repeating sequence, these repeated amino acid sequences can be assembled into β-folds, and the β-folds are arranged in an orderly manner and self-assembled into nano-crystals. The self-assembled nano-β-crystals of the silk peptide can be oxidized by ROS into a random curled structure and dissolved in water. The nano-crystals can be used as a ROS-responsive nano-drug delivery system, wherein the amino acid sequence of the silk peptide has been reported.

[0036] In the present invention, the mass ratio of the silk peptide nanocrystals to apigenin-7-O-glucoside is preferably 1:0.01-0.5, more preferably 1:0.1-0.3.

[0037] In the present invention, the particle size of the silk peptide nanocrystals is preferably 50-500 nm, more preferably 60-100 nm. In the present invention, the silk peptide nanocrystals are preferably in a corrugated layer, and the apigenin-7-O-glucoside in the silk peptide nanocrystals is preferably loaded between two adjacent layers of silk peptide nanocrystals.

[0038] The present invention provides a method for preparing the silk peptide nano-drug-carrying microcrystals described in the above technical solution, comprising the following steps: mixing an apigenin-7-O-glucoside solution with a silk peptide nano-crystal solution, and performing self-assembly to obtain a silk peptide nano-drug-carrying microcrystal. Fig.12 .

[0039] Unless otherwise specified, the materials and equipment used in the present invention are all commercially available products in the art.

[0040] The present invention uses silk peptide as self-assembly technology to load apigenin-7-O-glucoside onto silk peptide nanocrystals to prepare a nano drug delivery system, which has a protective effect on apigenin-7-O-glucoside and is also responsive to ROS.

[0041] In the present invention, the preparation method of the apigenin-7-O-glucoside solution preferably includes: mixing Echinops blue powder (dried) with ethanol aqueous solution to extract and obtain an extract; concentrating the extract to obtain an extract; freeze-drying the extract to obtain a freeze-dried powder; re-dissolving the freeze-dried powder, and separating the obtained freeze-dried powder solution by high performance liquid chromatography-tandem mass spectrometry to obtain apigenin-7-O-glucoside.

[0042] The present invention mixes the blue echinops powder (dried) with an ethanol solution for extraction to obtain an extract. In the present invention, the volume fraction of ethanol in the ethanol-water solution is preferably 30-100%, more preferably 50-75%; the dosage ratio of the blue echinops powder (dry weight) to the ethanol solution is preferably 1kg:1-10L, more preferably 1kg:2-5L. In the present invention, the extraction temperature is preferably 25-80°C, more preferably 50-60°C; the extraction time is preferably 6-20 h, more preferably 12-20 h; the extraction is preferably carried out under stirring conditions.

[0043] After the extraction is completed, the present invention preferably further comprises performing solid-liquid separation on the obtained extraction system to obtain an extract. The present invention has no particular limitation on the solid-liquid separation, and a solid-liquid separation method well known to those skilled in the art can be used, such as filtration; the purpose of the solid-liquid separation is to remove residues.

[0044] After obtaining the extract, the present invention concentrates the extract to obtain an extract. In the present invention, the concentration preferably includes rotary evaporation; the rotary evaporation temperature is preferably 25-80°C, more preferably 60-80°C; the rotary evaporation time is preferably 2-10 hours, more preferably 4-5 hours.

[0045] After obtaining the extract, the present invention freeze-dries the extract to obtain freeze-dried powder. In the present invention, the freeze-drying temperature is preferably -50 to 25°C, more preferably -20°C; the freeze-drying time is preferably 48 to 96 hours, more preferably 60 hours.

[0046] After obtaining the lyophilized powder, the present invention re-dissolves the lyophilized powder, and separates the obtained lyophilized powder solution by high performance liquid chromatography-tandem mass spectrometry to obtain apigenin-7-O-glucoside. In the present invention, the concentration of the lyophilized powder solution is preferably 20-100 mg / mL, more preferably 50-80 mg / mL; the solvent in the lyophilized powder solution preferably includes a lower alcohol aqueous solution, and the volume fraction of the lower alcohol in the lower alcohol aqueous solution is preferably 20-100%, more preferably 30-90%, and further preferably 40-50%; the lower alcohol preferably includes methanol and / or ethanol. In the present invention, the conditions for high performance liquid chromatography-tandem mass spectrometry separation preferably include: high performance liquid chromatography-tandem mass spectrometry separation conditions: separation is performed using a Vanquish UHPLC (ThermoScientific, Waltham, MA) ultra-high performance liquid chromatography system combined with an ACQUITY UPLC HSS T3 (2.1 mm ×100 mm, 1.8 µm) chromatographic column, with a column temperature of 35°C; a flow rate of 0.3 mL / min; mobile phase: mobile phase A is 0.1 v / v% formic acid aqueous solution, and mobile phase B is 0.1 v / v% formic acid-acetonitrile; the elution method is gradient elution, and the gradient elution program is shown in Table 1. The Q-Exactive HFX mass spectrometer was used to collect the primary and secondary spectra of the samples. The Q-Exactive HFX mass spectrometer sample was connected to the UHPLC system. The electrospray ionization (ESI) positive and negative ion modes were used for mass spectrometry acquisition. The spray voltage was 3800V (ESI+) / 3500V (ESI-), the sheath gas pressure was 45arb, the auxiliary gas pressure was 20arb, the ion transfer tube temperature was 320℃, and the nebulization temperature was 350℃. The detection mode was full scan / data-dependent secondary scan (Full-MS / dd-MS2) mode. The primary and secondary resolutions were 60000 and 15000, respectively. The top 10 MS1 ions obtained MS / MS spectra and collision energies (CEs). The step normalization energy levels were 20, 40, and 60; the primary mass-to-charge ratio scanning range was 90~1300. 2 μL of EC-sp solution was accurately aspirated and analyzed by LC-MS injection. The EC-sp sample was injected 5 times.

[0047] Table 1 Gradient elution program

[0048]

[0049] Apigenin-7-O-glucoside (AG) is the main anti-inflammatory active ingredient of Echinops cyanobacteria, which can accelerate the rapid repair of wound sites. AG has good antioxidant and anti-inflammatory effects, accelerates the recruitment and polarization of macrophages from M1 to M2, can not only reduce the infiltration of inflammatory cells at the site of injury, but also promote angiogenesis and accelerate wound repair. In the present invention, AG is prepared into a diabetic skin ulcer dressing by self-assembly technology, and AG regulates the inflammatory response and ROS content of the microenvironment at the diabetic skin ulcer site, thereby accelerating the damage repair of diabetic refractory ulcers.

[0050] In the present invention, the concentration of the apigenin-7-O-glucoside solution is preferably 10 μmol / L to 10 mmol / L, more preferably 1 to 5 mmol / L, and more preferably 2 to 3 mmol / L. In the present invention, the solvent in the apigenin-7-O-glucoside solution is preferably a phosphate buffer solution (PBS solution); the pH value of the PBS solution is preferably 7.

[0051] In the present invention, the preparation method of the silk peptide nanocrystal solution preferably comprises: dissolving the silk peptide nanocrystal in a PBS solution to obtain a silk peptide nanocrystal solution. In the present invention, the pH value of the PBS solution is 7. In the present invention, the concentration of the silk peptide nanocrystal solution is preferably 100 μmol / L to 10 mmol / L, more preferably 1 to 8 mmol / L, and more preferably 4 to 5 mmol / L.

[0052] In the present invention, the volume ratio of the apigenin-7-O-glucoside solution to the silk fibroin peptide nanocrystal solution is preferably 0.02-1:1, more preferably 0.5-1.5:1, and further preferably 1:1.

[0053] The present invention has no special limitation on the mixing of the apigenin-7-O-glucoside solution and the silk fibroin peptide nanocrystal solution, as long as the raw materials can be mixed evenly.

[0054] In the present invention, the temperature of the self-assembly is preferably 25~60°C, more preferably 37~50°C; the self-assembly is preferably carried out on a shaker; the rotation speed of the shaker is preferably 100~1000r / min, more preferably 500~600r / min; the time of the self-assembly is preferably 1~12h, more preferably 5~8h.

[0055] In the present invention, the apigenin-7-O-glucoside solution is mixed with the silk peptide nanocrystal solution for self-assembly to obtain a silk peptide nanocrystal solution, which is a colloidal white solution containing silk peptide nanocrystals.

[0056] In a specific embodiment of the present invention, the apigenin-7-O-glucoside solution, the silk fibroin peptide nanocrystal solution and the silk fibroin peptide nanocrystals loaded with drugs are preferably stored at 4° C. for future use.

[0057] The present invention provides a method for preparing a broad-spectrum antioxidant silk fibroin asymmetric hydrogel, comprising the following steps:

[0058] A solution of silk fibroin peptide nano-drug-carrying microcrystals, a silk fibroin solution and a nano-silver solution are mixed to obtain a mixed solution; the silk fibroin peptide nano-drug-carrying microcrystals are the silk fibroin peptide nano-drug-carrying microcrystals described in the above technical solution or the silk fibroin peptide nano-drug-carrying microcrystals prepared by the preparation method described in the above technical solution;

[0059] A voltage is applied to the mixed solution to obtain a broad-spectrum antioxidant silk asymmetric hydrogel.

[0060] The invention mixes a solution of silk fibroin peptide nano drug-carrying microcrystals, a silk fibroin solution and a nano silver solution to obtain a mixed solution.

[0061] In the present invention, the concentration of the solution of the silk peptide nano-drug-carrying microcrystals is preferably 1-20 mg / mL, more preferably 5-10 mg / mL.

[0062] In the present invention, the concentration of the silk fibroin solution is preferably 1-100 mg / mL, more preferably 10-60 mg / mL. The present invention has no special requirements for the specific preparation method of the silk fibroin solution, and a method well known to those skilled in the art can be used.

[0063] In a specific embodiment of the present invention, the method for preparing the silk fibroin solution preferably comprises: degumming natural mulberry silk to obtain silk; dissolving the silk in a solvent to obtain a mixed solution; and sequentially performing dialysis treatment and purification treatment on the mixed solution to obtain a silk fibroin solution. In the present invention, the degumming preferably comprises: mixing and boiling natural mulberry silk, sodium carbonate and boiling water. In the present invention, the mass ratio of the natural mulberry silk to sodium carbonate is preferably 1:0.5~1.5, more preferably 1:0.8~1. In the present invention, the boiling time is preferably 20~40min, more preferably 30min; the boiling is preferably carried out under stirring conditions. After the degumming, the present invention preferably further comprises washing the degummed silk with water and then drying to obtain silk. In the present invention, the solvent preferably includes a lithium bromide solution or a calcium chloride ternary solution; the concentration of the lithium bromide solution is preferably 8-12 mol / L, more preferably 9.3 mol / L; the composition of the calcium chloride ternary solution preferably includes calcium chloride, ethanol and water; the molar ratio of calcium chloride, ethanol and water is preferably 1:2:8. In the present invention, the dissolution temperature is preferably 50-70°C, more preferably 60°C; the dissolution time is preferably 3-5h, more preferably 4h. In the present invention, the dialysis treatment preferably includes water dialysis, and the molecular weight cutoff of the dialysis bag used in the dialysis treatment is preferably 3500Da; the dialysis time is preferably 2-4d, more preferably 3d; during the dialysis treatment, the water is preferably replaced every 2-4h (more preferably 3h); the water preferably includes deionized water. In the present invention, the purification preferably includes centrifugal separation, and the supernatant is a protein solution; the rotation speed of the centrifugal separation is preferably 8000~10000r / min, more preferably 9000r / min; the time of the centrifugal separation is preferably 20~40min, more preferably 30min; the temperature of the centrifugal separation is preferably 1~5°C, more preferably 4°C.

[0064] In the present invention, the concentration of the nanosilver solution is preferably 1-10 mg / mL, more preferably 3-8 mg / mL, and further preferably 5-6 mg / mL.

[0065] In the present invention, the method for preparing the nano silver solution preferably comprises: mixing silver nitrate, water, isopropanol and glucose, and performing a reduction reaction to obtain a nano silver solution. In the present invention, the glucose is preferably powdered glucose. In the present invention, the mixing of silver nitrate, water, isopropanol and glucose preferably comprises: mixing silver nitrate with part of the water to obtain a silver nitrate solution; mixing glucose with the remaining water to obtain a glucose solution; heating the silver nitrate solution to the temperature of the reduction reaction, and sequentially adding isopropanol and glucose solution. In the present invention, the concentration of the silver nitrate solution is preferably 0.1~10wt%, more preferably 0.5~5wt%. In the present invention, the concentration of the glucose solution is preferably 5~10wt%, more preferably 6~9wt%, and further preferably 7~8wt%. In the present invention, the volume ratio of the silver nitrate solution to isopropanol is preferably 1:0.01~1, more preferably 1:0.1~0.5; the mass ratio of the silver nitrate to glucose is preferably 1:1~2, more preferably 1:1.5~2. In the present invention, the temperature of the reduction reaction is preferably 25-100°C, more preferably 50-80°C; the time of the reduction reaction is preferably 30-300min, more preferably 60-100min. In the present invention, preferably after the reduction reaction, the obtained reaction system is centrifuged to remove the aggregated nanosilver particles to obtain a nanosilver solution. In the present invention, the speed of the centrifugation is preferably 1000-5000g, more preferably 2000-4000g; the time of the centrifugation is preferably 1-30min, more preferably 5-20min. Diabetic wounds are difficult to heal, and the sugar content in the wound microenvironment is relatively high, which is easy to cause infection. The present invention introduces broad-spectrum antibacterial nanosilver into the hydrogel dressing, so that it has both antioxidant and anti-inflammatory effects and broad-spectrum antibacterial effects.

[0066] In the present invention, the mass ratio of the silk fibroin peptide nano-drug-carrying microcrystals to the silk fibroin in the silk fibroin solution is preferably 0.02-0.2:1, more preferably 0.05-0.15:1, and further preferably 0.1:1.

[0067] In the present invention, the mass ratio of the silk peptide nano-drug-carrying microcrystals to the nano-silver in the nano-silver solution is preferably 2-20:1-10, more preferably 5-10:5-10, and further preferably 1:1.

[0068] In the present invention, the mixing of the solution of the silk peptide nano drug-carrying microcrystals, the silk protein solution and the nano silver solution preferably comprises: dropping the solution of the silk peptide nano drug-carrying microcrystals into the silk protein solution, and then adding the nano silver solution. In the present invention, the nano silver solution is preferably added dropwise. In the present invention, the silk protein solution is preferably heat-treated before use, the heat treatment temperature is preferably 50-70°C, more preferably 60°C, the heating time is preferably 10-15h, more preferably 12h, and the silk protein solution after heat treatment is viscous.

[0069] After obtaining the mixed solution, the present invention applies voltage to the mixed solution to obtain a broad-spectrum antioxidant silk asymmetric hydrogel. In the present invention, the voltage is preferably 10-100V, more preferably 50-80V; the time for applying the voltage is preferably 30-300min, more preferably 50-120min. In the present invention, during the voltage application process, the silk fibroin moves in the electric field.

[0070] The present invention preferably performs freeze drying after applying voltage to obtain a broad-spectrum antioxidant silk asymmetric hydrogel. In the present invention, the freeze drying temperature is preferably -50 to 4°C, more preferably -20°C; the freeze drying time is preferably 48 to 96 hours, more preferably 50 to 60 hours. In a specific embodiment of the present invention, the broad-spectrum antioxidant silk asymmetric hydrogel is a porous dry gel sponge.

[0071] The present invention provides a broad-spectrum antioxidant silk asymmetric hydrogel prepared by the preparation method described in the above technical scheme, wherein the broad-spectrum antioxidant silk asymmetric hydrogel has a dense surface and a loose surface. In the present invention, the porosity of the dense surface is 20~40%, preferably 25~35%, and further preferably 30%; the porosity of the loose surface is 50~80%, preferably 60~70%.

[0072] The present invention provides the use of the broad-spectrum antioxidant silk asymmetric hydrogel described in the above technical solution in the preparation of a dressing, wherein the dressing preferably includes a diabetic skin ulcer dressing.

[0073] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0074] The pH of the PBS solution used in the following test examples is 7.

[0075] Example 1

[0076] Preparation of apigenin-7-O-glucoside:

[0077] 1 kg of dried blue echinops powder was mixed with 2 L of 75 wt % ethanol, heated to 60 °C and mechanically stirred, extracted for 12 hours, filtered, and the residue was removed. The obtained extract was rotary evaporated at 80 °C for 4 hours to evaporate the ethanol to obtain an extract, which was frozen at -20 °C for 12 hours and freeze-dried in a freeze dryer for 72 hours to obtain a lyophilized powder. The lyophilized powder was dissolved in a 40 v / v% methanol aqueous solution, vortexed for 30 seconds, centrifuged at 16000 g and 4 °C for 15 minutes, and the supernatant was a lyophilized powder solution. The lyophilized powder solution was separated by high performance liquid chromatography-tandem mass spectrometry to obtain apigenin-7-O-glucoside. The solid-liquid ratio of the lyophilized powder to the methanol aqueous solution was 20 mg: 0.3 mL.

[0078] HPLC-MS / MS separation conditions: Vanquish UHPLC (Thermo Scientific, Waltham, MA) ultra-high performance liquid chromatography system combined with ACQUITY UPLC HSS T3 (2.1 mm × 100 mm, 1.8 µm) column was used for separation. The column temperature was 35 °C. The flow rate was 0.3 mL / min. The mobile phases were: mobile phase A was 0.1 v / v% formic acid in water, and mobile phase B was 0.1 v / v% formic acid-acetonitrile. The elution mode was gradient elution. The gradient elution program is shown in Table 1. The Q-Exactive HFX mass spectrometer was used to collect the primary and secondary spectra of the samples. The Q-Exactive HFX mass spectrometer sample was connected to the UHPLC system. The electrospray ionization (ESI) positive and negative ion modes were used for mass spectrometry acquisition. The spray voltage was 3800V (ESI+) / 3500V (ESI-), the sheath gas pressure was 45arb, the auxiliary gas pressure was 20arb, the ion transfer tube temperature was 320℃, and the nebulization temperature was 350℃. The detection mode was full scan / data-dependent secondary scan (Full-MS / dd-MS2) mode. The primary and secondary resolutions were 60000 and 15000, respectively. The top 10 MS1 ions obtained MS / MS spectra and collision energies (CEs). The step normalization energy levels were 20, 40, and 60; the primary mass-to-charge ratio scanning range was 90~1300. 2 μL of EC-sp solution was accurately aspirated and analyzed by LC-MS injection. The EC-sp sample was injected 5 times.

[0079] Preparation of silk peptide nanocrystals:

[0080] 5 mL of 2 mmol / L apigenin-7-O-glucoside solution was prepared with a phosphate buffer solution at a pH of 7, and magnetic stirring was performed for 30 min. 5 mL of 4 mmol / L silk peptide (GAGAGS) 2 nanocrystal solution prepared with a phosphate buffer solution at a pH of 7 was added, mixed evenly, and placed on a shaker at 37°C and 600 rpm / min for 8 h to obtain a colloidal white solution containing silk peptide nano-drug-loaded microcrystals.

[0081] Preparation of nanosilver solution:

[0082] Weigh 50 mg of silver nitrate and dissolve it in 10 mL of deionized water, and stir it magnetically for 30 minutes; heat it to 80°C, add 1 mL of isopropanol, and continue stirring for 10 minutes to obtain a mixed solution of silver nitrate and isopropanol; dissolve 100 mg of glucose powder in 1 mL of deionized water, add it to the mixed solution of silver nitrate and isopropanol after it is fully dissolved, continue stirring for 60 minutes, and centrifuge it at 2000g for 5 minutes to remove the aggregated nanosilver particles to obtain a nanosilver solution.

[0083] Preparation of asymmetric silk-based hydrogel raw material solution:

[0084] 2 L of deionized water was added to a water bath, heated to 100 °C, and then 4.24 g of anhydrous sodium carbonate and 5 g of natural mulberry silk were added, and the mixture was boiled for 30 min to remove the sericin in the natural silk thread, and the mixture was stirred at intervals during the heating process. The de-sericin-free silk was repeatedly rinsed with deionized water, and then dried in an oven at 60 °C to obtain silk. 9.3 mol / L lithium bromide solution was added to the silk at a ratio of 27 g:100 mL of silk to lithium bromide solution, and the silk was sealed with plastic wrap and pierced, and then dried at 60 °C for 4 h. The obtained silk solution was placed in a dialysis bag (dialysis bag with a molecular weight cutoff of 3500 Da), sealed at both ends, and dialyzed in deionized water for 3 d. The deionized water was replaced every 3 h during the dialysis process. The dialyzed silk fibroin solution was divided into 50 mL centrifuge tubes and centrifuged at a speed of 9000 r / min and a time of 30 The mixture was centrifuged at 4°C for 10 min and 4°C, the lower precipitate was discarded, the supernatant was collected to obtain a silk fibroin solution, and the solution was stored in a 4°C refrigerator. The concentration of the silk fibroin solution was measured by the BCA method, and the concentration of the obtained silk fibroin solution was 60 mg / mL.

[0085] 10 mL of 60 mg / mL silk fibroin solution was placed in a 60°C forced air oven for 12 h. After the solution became viscous, 1 mL of the colloidal white solution containing silk peptide nano-drug-carrying microcrystals was dropped into the silk fibroin solution and magnetically stirred for 60 min. After the colloidal white solution was fully dispersed in the silk fibroin solution, a mixture was obtained. 1 mL of the nanosilver solution was dropped into the mixture and magnetically stirred for 60 min to obtain an asymmetric silk fibroin-based hydrogel raw material solution.

[0086] Preparation of broad-spectrum antioxidant silk asymmetric hydrogel:

[0087] The asymmetric silk-based hydrogel raw material solution was subjected to a uniform electric field with a voltage of 50 V. After reacting for 2 hours, a broad-spectrum antioxidant silk asymmetric hydrogel (abbreviated as SF@β-crystallite / AG-Ag) was prepared. SF@β-crystallite / AG-Ag was freeze-dried in a freeze dryer for later use. The broad-spectrum antioxidant silk asymmetric hydrogel has a dense surface (porosity of 30%) and a loose porous surface (porosity of 70%).

[0088] Test Example 1

[0089] The characterization picture of the colloidal white solution containing silk peptide nano drug-carrying microcrystals prepared in Example 1 is as follows: Figure 1 As shown, Figure 1 A in the middle is an infrared spectrum, from which it can be seen that the silk peptide nano-drug-carrying microcrystals are β-folded and β-antiparallel folded structures. Figure 1 B is an atomic force microscope image. Figure 1 C in the middle is a transmission electron microscope image, from which it can be seen that the topological structure of the colloidal white solution is a nanosheet structure.

[0090] The transmission electron microscope image of the nano silver particles prepared in Example 1 is as follows: Figure 2 As shown, it can be seen that the size of the nanosilver particles is 10~20nm.

[0091] The scanning electron microscopy (SEM) of the broad-spectrum antioxidant silk asymmetric hydrogel prepared in Example 1 is as follows: Figure 3 As shown, A represents the loose surface and B represents the dense surface. From the topological structure characterization of the broad-spectrum antioxidant silk asymmetric hydrogel, it can be seen that the broad-spectrum antioxidant silk asymmetric hydrogel has an interpenetrating pore structure, with one surface being loose and the other surface being dense.

[0092] Test Example 2

[0093] The SF@β-crystallite / AG-Ag prepared in Example 1 was tested by rheometer at 25°C for three cycles to record the changes in G' and G". Figure 4 It can be seen that the mechanical strength of SF@β-crystallite / AG-Ag hydrogel is 900Pa, which is suitable for skin damage repair.

[0094] Test Example 3

[0095] The SF@β-crystallite / AG-Ag prepared in Example 1 was immersed in a PBS solution and placed in an incubator at 37°C to obtain SF@β-crystallite / AG-Ag extract (concentration of 0.1 g / mL) with 3 samples in each group. Samples were taken at 3h, 6h, 9h, 12h, 24h, 36h, 48h, 60h and 72h of incubation (the control group was gauze-AG-Ag, and apigenin-7-O-glucoside AG and Ag were adsorbed on the gauze, the mass of AG accounted for 10% of the mass of the gauze, and the mass of Ag accounted for 10% of the mass of the gauze). The content of apigenin-7-O-glucoside was determined by a UV spectrophotometer, and the protein sustained-release curve was drawn. The experimental results are shown in Figure 5 It can be seen that SF@β-crystallite / AG-Ag hydrogel has good drug sustained release ability.

[0096] Test Example 4

[0097] The SF@β-crystallite / AG-Ag prepared in Example 1 was immersed in physiological saline and incubated at 37°C for 72 hours to obtain the SF@β-crystallite / AG-Ag extract (concentration of 0.1 g / mL). L929 cells were cultured to the logarithmic growth phase at 37°C, and CCK-8 was used to detect cell activity and proliferation on the 1st, 2nd, 3rd, 4th, 5th, 6th and 7th days. Figure 6 In A, SF@β-crystallite is a mixture of silk fibroin and silk peptide (GAGAGS) 2 nanocrystals, and the ratio of the two is the same as in Example 1, and SF is silk fibroin. Guinea pigs were anesthetized by intraperitoneal injection of 2% sodium pentobarbital. After hair removal, 100 μL of SF@β-crystallite / AG-Ag extract was injected intradermally (the control group was saline, control), and photos were taken at 0h, 12h, 24h, 48h and 72h. Figure 6 In B, there is no injection in the first 0h, and the second 0h is the injection of SF@β-crystallite / AG-Ag extract. Figure 6 It can be seen that SF@β-crystallite / AG-Ag extract hydrogel is non-cytotoxic and non-sensitizing.

[0098] Test Example 5

[0099] SF@β-crystallite / AG-Ag was incubated in physiological saline for 72 h to obtain SF@β-crystallite / AG-Ag extracts with concentrations of 5 μM, 10 μM, 20 μM, 40 μM, and 80 μM, respectively.

[0100] 200 μL of SF@β-crystallite / AG-Ag extract (concentrations of 5 μM, 10 μM, 20 μM, 40 μM, and 80 μM, respectively, obtained by incubation for 72 h in saline) was incubated with 100 μL of 100 mM H2O2 at 37 °C for 1 h. After the reaction, the amount of residual H2O2 was determined according to the method in the kit instructions, and the H2O2 removal efficiency of the hydrogel was calculated, see Figure 7 It can be seen that SF@β-crystallite / AG-Ag hydrogel has a good ability to remove hydrogen peroxide.

[0101] 200 μL of SF@β-crystallite / AG-Ag extract (concentrations of 5 μM, 10 μM, 20 μM, 40 μM, and 80 μM, respectively) was added to a 24-well plate with 200 μL of Fenton reagent and 200 μL of TMB under light-proof conditions, and reacted at 37°C for 30 min. The absorption peak of the solution at 652 nm was monitored using an ELISA reader (Synergy h1, Biotek, Winooski, VT, USA). The ability of the hydrogel to scavenge hydroxyl radicals was calculated, see Figure 8 It can be seen that SF@β-crystallite / AG-Ag extract hydrogel has a good ability to scavenge hydroxyl radicals.

[0102] 200 μL of SF@β-crystallite / AG-Ag extract (concentrations were 5 μM, 10 μM, 20 μM, 40 μM, and 80 μM, respectively) was added to 1 mL of superoxide anion radical solution, and after adding 2 mL of color developer and standing for 10 min, the absorbance was detected at 550 nm. The ability of the hydrogel to scavenge superoxide anion radicals was calculated, see Fig. 9 It can be seen that SF@β-crystallite / AG-Ag hydrogel has a good ability to remove cationic anions.

[0103] Test Example 6

[0104] SF@β-crystallite / AG-Ag was placed in a PBS solution and incubated for 72 h to obtain a SF@β-crystallite / AG-Ag extract with a concentration of 0.1 g / mL.

[0105] NIH 3T3 cells were plated at 5 × 10 5The cells were inoculated at a density of 100 cells / mL into a 6-well plate pretreated with 0.1% gelatin for 2 h and cultured at 37°C for 12 h. The SF@β-crystallite / AG-Ag extract was added to the wells of each group of 6-well plates, and then the cells were treated with 100 μM H2O2 and incubated at 37°C for 30 min. Under light-proof conditions, 1 mL of 10 μM DCFH-DA serum-free medium dye was added to each well of cells (the cells in the control group were added with serum-free medium), incubated at 37°C for 20 min, washed twice with serum-free medium, observed and imaged using a confocal microscope (Nikon A1, Japan), and then NIS Element AR software (version 5.30.03) was used to quantitatively analyze the fluorescence intensity of ROS stained green in the cells for statistical analysis. Cells without H2O2 were used as the control group. The experimental results are shown in Fig.10 Among them, A is the intracellular reactive oxygen fluorescence image, and B is the statistical graph of intracellular reactive oxygen fluorescence intensity. It can be seen that SF@β-crystallite / AG-Ag hydrogel has a good ability to remove intracellular reactive oxygen.

[0106] Test Example 7

[0107] 70 male SD rats (280-320 g) were purchased from Beijing Weitonglihua Experimental Animal Technology Co., Ltd. and were placed in an SPF environment at room temperature (25°C) with a 12-h light / dark cycle and free access to water and food. One week later, the rats were fed a high-sucrose and high-fat diet for 8 weeks, and 2% streptozotocin (STZ, 35 mg / kg, Sigma) was injected intraperitoneally in the 9th week. Fasting blood glucose and body weight were recorded weekly. Rats with fasting blood glucose >11.5 mmol / L and lasting for more than 4 weeks were judged to be type II diabetic rats. If the fasting blood glucose was lower than 11.5 mmol / L, 2% STZ was injected intraperitoneally again. During the process of inducing the diabetic model, the changes in body weight and blood glucose of diabetic rats were recorded from 1 to 12 weeks.

[0108] Type II diabetic SD rats (male, 60 rats) were randomly divided into 4 groups, 15 rats in each group. The diabetic SD rats were anesthetized by intraperitoneal injection of 1% sodium pentobarbital (30 mg / kg), the dorsal hair was removed, the dorsal skin was disinfected, and the dorsal skin was cut with ophthalmic scissors to cause deep fascia layer skin injury (25 mm in diameter). The experimental groups were as follows: control group: gauze treatment group; experiment 1: SF treatment group; experiment 2: SF@β-crystallite treatment group; experiment 3: SF@β-crystallite / AG-Ag treatment group. The wound was treated twice a week for disinfection, dressing change, and wound dressing. The wound healing process was recorded by taking photos on days 0, 3, 7, 10, 14, 17, 21, and 24. The wound size was calculated using Image J software and the healing rate curve was drawn.

[0109] Fig.11The actual photo of the broad-spectrum antioxidant silk asymmetric hydrogel prepared in Example 1 treating full-thickness skin lesions in diabetic rats shows that SF@β-crystallite / AG-Ag hydrogel has a good effect in treating diabetic wounds.

[0110] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. Application of silk peptide nano-crystals and nano-silver in the preparation of drugs for treating diabetic wound healing and repairing, wherein the silk peptide nano-crystals include silk peptide nano-crystals and apigenin-7-O-glucoside loaded in the silk peptide nano-crystals; the silk peptide nano-crystals have β-folding and β-antiparallel folding structures, and the topological structure is a nano-sheet structure; the mass ratio of the silk peptide nano-crystals to apigenin-7-O-glucoside is 1:0.01~0.

5.

2. A method for preparing a broad-spectrum antioxidant silk asymmetric hydrogel for treating diabetic wounds, comprising the following steps: Mixing a solution of silk peptide nano drug-carrying microcrystals, a silk fibroin solution and a nanosilver solution to obtain a mixed solution; The silk fibroin peptide nano-drug-carrying microcrystals are the silk fibroin peptide nano-drug-carrying microcrystals used in the application of claim 1; A voltage is applied to the mixed solution to obtain a broad-spectrum antioxidant silk asymmetric hydrogel; the voltage is 10-100V; and the voltage application time is 30-300min.

3. The preparation method according to claim 2, characterized in that: The mass ratio of the silk fibroin peptide nano drug-carrying microcrystals to the silk fibroin in the silk fibroin solution is 0.02-0.2:

1.

4. The preparation method according to claim 2, characterized in that: The mass ratio of the silk peptide nano drug-carrying microcrystals to the nano silver in the nano silver solution is 2-20:1-10.

5. The preparation method according to claim 2, characterized in that: The mixing comprises: dropping a solution of silk peptide nano drug-carrying microcrystals into a silk protein solution, and then adding a nano silver solution.

6. The broad-spectrum antioxidant silk asymmetric hydrogel prepared by the preparation method according to any one of claims 2 to 5, wherein the broad-spectrum antioxidant silk asymmetric hydrogel has a dense surface and a loose surface; the porosity of the dense surface is 20 to 40%; and the porosity of the loose surface is 50 to 80%.

7. Use of the broad-spectrum antioxidant silk asymmetric hydrogel according to claim 6 in preparing dressings.

Citation Information

Patent Citations

  • Silk-based product formulations and methods of use

    CN112533626A

  • Preparation of silk fibroin peptide self-assembled drug-loaded nanoparticles and kidney protection effect of silk fibroin peptide self-assembled drug-loaded nanoparticles

    CN114712311A

  • Preparation method and application of deformable silk fibroin gradient hydrogel

    CN116948213A